Clinical Applications of Radiomics in Nuclear Medicine - Lohmann, Philipp; Bundschuh, Ralph Alexander; Miederer, Isabelle; Mottaghy, Felix M.; Langen, Karl Josef; Galldiks, Norbert (Nuklearmedizin - NuclearMedicine, 2023)
Radiomics is an emerging field of artificial intelligence that focuses on the extraction and analysis of quantitative features such as intensity, shape, texture and spatial relationships from medical images. These features, often imperceptible to the human eye, can reveal complex patterns and biological insights. They can also be combined with clinical data to create predictive models using machine learning to improve disease characterization in nuclear medicine. This review article examines the current state of radiomics in nuclear medicine and shows its potential to improve patient care. Selected clinical applications for diseases such as cancer, neurodegenerative diseases, cardiovascular problems and thyroid diseases are examined. The article concludes with a brief classification in terms of future perspectives and strategies for linking research findings to clinical practice.
Keywords: PET; SPECT; Artificial Intelligence (AI); Machine Learning; Cancer; Neurodegenerative Disease; Cardiovascular Disease; Thyroid Diseases